Unlocking the clinical potential of paired inspiratory and expiratory CT scans in the differential diagnosis of cystic lung diseases: A systematic review. - Lucas Gabriel R Pinheiro; Carlos Augusto Treviso; Gabriele Carra Forte; Enrico Mattana Muller; Bruno Hochhegger; Rubens Gabriel Feijó Andrade (PLoS ONE)
Introduction Currently, high-resolution computed tomography (HRCT) is the imaging of choice for the differential diagnosis of various cystic lung lesions, including true cystic lung diseases (CLD) and lesions that may mimic them. However, the traditionally used inspiratory scan still presents a significant spectrum of overlapping radiological features. Recent studies have demonstrated variation in lesion size between inspiratory and expiratory phases, probably due to cyst-airway communication. In this study, we aimed to conduct a systematic review of paired inspiratory and expiratory HRCT in the assessment of cystic lesions as an additional tool to narrow the differential diagnosis. Methods A systematic search was performed in PubMed, Scopus, EMBASE, BVS, and Cochrane through August 2023. Full-text articles that performed paired inspiratory and expiratory CT scans in adult patients with cystic lung lesions were included, with the outcome measured as the reduction in lesion size according to the respiratory phase. Diagnoses were confirmed through histopathological or radiological features. Results Out of the 96 records, three studies met the criteria for inclusion and were analyzed, comprising a total of 149 participants and 513 cystic lesions. Pulmonary Langerhans Cell Histiocytosis (PLCH), Lymphangioleiomyomatosis (LAM) honeycombing and cystic bronchiectasis became considerably smaller during expiratory CT scans, while the size of emphysema tended to remain constant during respiratory cycles. Conclusions This study has suggested that paired inspiratory and expiratory CT scans can be valuable for helping differentiate between emphysema and other diseases with a cystic pattern due to their ability to reveal dynamic properties of the lesions. However, the average reduction in cyst size as a single parameter is not sufficient for further refining diagnostics. Studies exploring advanced metrics to assess the reduction in lesion diameter emerge as potential opportunities to investigate the cyst-airway communication hypothesis and further enhance the diagnostic accuracy of paired methods.